Українська історіографія відновлення і утвердження другої Речі Посполитої - Шумихіна, С. (Спеціальні історичні дисципліни: питання теорії та методики, 2007)
В статье анализируются работы западноукраинских и русских историков, посвященные истории Польши междувоенного периода. Исследуются различные подходы к изучению ряда проблем, связанных с политическими, социальными и культурными процессами в жизни страны. The article presents analysis of both Western Ukrainian and Russian researches devoted to Polish history in-between two World Wars. The research allowed to investigate and describe the difference in approaches the given problematic, which is due to political, social and cultural process in the country.